Air–Rail Connectivity Index: A Comprehensive Study of Multimodal Journeys - Clara Buire; Slavica Dožić; Danica Babić; Ismini Stroumpou; Josep L. Larriba; Esteban Gatein; Ruth Parajó (Engineering Proceedings)
To enhance the accessibility and efficiency of airports, the concept of airport connectivity is extended to High-Speed Rail (HSR), as major hub airports now have direct access to an HSR station. The traditional hub connectivity index is supplemented by the number and quality of connections between train and flight departures/arrivals (or timetables). The methodology is tested at the Paris-Charles de Gaulle airport. The results highlight that air–rail and rail–air connections can represent up to 72% of the total hub connectivity. A disaggregated analysis of connectivity across origin–destination pairs was conducted, revealing potential synchronization gaps. These findings demonstrate that this tool can assist transportation service providers in synchronizing their timetables, by measuring the degree to which it contributes to improve connectivity. Moreover, the findings offer new insights into air–rail timetable coordination and provide policy implications regarding the replacement of feeder flights by HSR.